Women and leadership in higher education - Longman, Karen; Madsen, Susan R. (Women and leadership (Charlotte, N.C.), 2014)
Women and Leadership in Higher Education is the first volume in a new series of books (Women and Leadership: Research, Theory, and Practice) that will be published in upcoming years to inform leadership scholars and practitioners. This book links theory, research, and practice of women's leadership in various higher education contexts and offers suggestions for future leadership development strategies. This volume focuses on the field of higher education, particularly within the context of the United States--a sector that serves a majority of students at all degree levels who are women, yet lacks parity by women in senior leadership roles.The book's fifteen chapters present both hard facts regarding the current demographic realities within higher education and fresh thinking about how progress can and must be made in order for U.S. higher education to benefit from the perspectives of women at the senior leadership table. The book's opening section provides data and analysis in addressing "The State of Women and Leadership in Higher Education"; the second section offers descriptions of three effective models for women's leadership development at the national and institutional levels; the third section draws from recent research to present "Women's Experiences and Contributions in Higher Education Leadership." The book concludes with five shorter chapters written by current and former college and university presidents who offer "Lessons from the Trenches" for the benefit of those who follow. In short, the thesis of the book is that our world is changing; higher education collectively, as well as institutions of all types, must change. Bringing more women into leadership is critical to the goal of moving our society and world forward in healthier ways.